Changes in Bladder Health over Time: A Longitudinal Analysis of Adult Women in the Boston Area Community Health Survey. Issue 5 (30th May 2022) - Sutcliffe, Siobhan; Cain, Charles; Bavendam, Tamara; Fitzgerald, Colleen M.; Gahagan, Sheila; Markland, Alayne D.; Shoham, David A.; Smith, Ariana L.; Rudser, Kyle; ,
Abstract : Purpose: Our goal was to describe changes in bladder health, defined as "a complete state of physical, mental, and social well-being related to bladder function that permits daily activities, adapts to short-term stressors, and allows optimal well-being, " in women over time. Materials and Methods: We used data on 15 lower urinary tract symptoms (LUTS) and interference from urinary experiences assessed at the baseline and 5-year followup interviews of the BACH (Boston Area Community Health) Survey to estimate changes in bladder health over time in women. Associations between baseline and followup bladder health (defined as the maximum frequency of LUTS or interference at each time point) were calculated by ordinal logistic regression and generalized linear models. Results: A total of 2, 526 women provided complete information on bladder health at baseline and followup. Over the 5-year followup, 6.5% of women maintained optimal bladder health (no LUTS or interference), 33.6% developed worse bladder health (including 10.4% who transitioned from optimal to less than optimal health), 31.4% maintained their less than optimal bladder health status and 28.7% improved. Despite these changes, women with poorer bladder health at baseline were still more likely to have poorer bladder health 5 years later (eg multivariable-adjusted relative risk=3.27, 95% confidence interval: 2.49–4.29 for severe LUTS/interference at followup among those with severe LUTS/interference at baseline). Conclusions: Findings from our large secondary analysis of BACH Survey data suggest considerable variability in bladder health over time, and underscore the importance of bladder health promotion to prevent the initial onset and progression of poor bladder health in women.